Perlindungan Hak Wajib Pajak Dalam Proses Pemeriksaan Dan Penegakan Hukum Pajak Di Indonesia Ditinjau Dari Perspektif Hukum Dan Etika - Syavira Alzena Qinayya; Alvieta Alice Reyhanif; Dimas Dwi Nugroho; Muhammad Bondhi Alby Maulana (Universitas Sains dan Teknologi Komputer, 2024)
To encourage voluntary compliance with tax obligations, taxpayers must be treated fairly, which requires legal protection of their rights. The charter of taxpayer rights or the actual tax law as contained in the tax law are two methods used to implement the recognition of taxpayer rights. Taxpayers themselves also submit restitution claims, one of which is value-added tax, in this case the legal certainty does not exist because of the overlapping administrative and criminal sanctions. Some countries have explicitly recognized taxpayer rights in their laws, as well as through the creation of papers outlining those rights. The